2022
DOI: 10.1155/2022/8453470
|View full text |Cite|
|
Sign up to set email alerts
|

A Secure Private Cloud Storage Platform for English Education Resources Based on IoT Technology

Abstract: The contemporary ubiquitous “cloud” network knowledge and information resources, as well as ecological pedagogy theory, have enlarged teaching research’s perspective, widened teaching research’s innovation area, and created practical options for English classroom reform. Cloud education relies on the Internet of Things, cloud computing, and big data to have a huge impact on the English learning process. The key to the integration of English education resources is the storage of huge amount of English teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…College students propose English learning materials to other students by registering the personalized learning platform's resource pool and calculating the user set using the collaborative filtering algorithm [35]. Figure 5 depicts the process of the personalized learning platform's recommendation model for College English [36].…”
Section: Recommendation Of Personalized College English Learning Reso...mentioning
confidence: 99%
“…College students propose English learning materials to other students by registering the personalized learning platform's resource pool and calculating the user set using the collaborative filtering algorithm [35]. Figure 5 depicts the process of the personalized learning platform's recommendation model for College English [36].…”
Section: Recommendation Of Personalized College English Learning Reso...mentioning
confidence: 99%
“…The key to integrating online educational resources lies in the storage of massive teaching data. Wei et al [34] applied cloud storage technologies and methods to the construction of integrated online educational resources, which effectively saves educational resources for schools, enhances the utilization of online educational resources and thereby improves the teaching quality of subjects. Hui Tao [35] proposed an online English teaching system approach based on IoT technology.…”
Section: Related Workmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%